2011
DOI: 10.1093/brain/awr055
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of cognitive impairment in posterior cortical atrophy

Abstract: With the prospect of disease-modifying drugs that will target the physiopathological process of Alzheimer's disease, it is now crucial to increase the understanding of the atypical focal presentations of Alzheimer's disease, such as posterior cortical atrophy. This study aimed to (i) characterize the brain perfusion profile in posterior cortical atrophy using regions of interest and a voxel-based approach; (ii) study the influence of the disease duration on the clinical and imaging profiles; and (iii) explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
139
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(160 citation statements)
references
References 58 publications
16
139
0
5
Order By: Relevance
“…However, the results support the conclusion that memory impairment can be detected at initial presentation with a simple screening instrument, and with a relatively short average symptom duration compared to other studies (for example, [6,10]). Despite differences in the predominant clinical symptoms in PCA and EOAD, the concomitant and significant memory impairment early in the clinical course may reflect the common underlying AD pathology.…”
Section: Discussionsupporting
confidence: 82%
“…However, the results support the conclusion that memory impairment can be detected at initial presentation with a simple screening instrument, and with a relatively short average symptom duration compared to other studies (for example, [6,10]). Despite differences in the predominant clinical symptoms in PCA and EOAD, the concomitant and significant memory impairment early in the clinical course may reflect the common underlying AD pathology.…”
Section: Discussionsupporting
confidence: 82%
“…Data from functional imaging studies using single photon emission computed tomography (SPECT) and fluorodeoxyglucose positron emission tomography (FDG-PET) are largely consistent with structural changes in parieto-occipital areas (see Figure 2) 20,[47][48][49][50]51 . In addition to posterior regions, FDG-PET has revealed specific areas of hypometabolism in the frontal eye fields bilaterally which may occur secondary to loss of input from occipitoparietal regions and underpin ocular apraxia in PCA 20,52 .…”
Section: Neuroimagingmentioning
confidence: 81%
“…Age at onset tends to be much earlier in PCA than in typical amnestic AD, with most studies reporting PCA symptom onset in patients' mid 50s and early 60s 17,19 although some studies have reported a wider age spread (45-74 years 20 , 40-86 years 21 ). In terms of gender distribution, some studies have reported no difference in the prevalence based on gender 15,17,19 , whereas others have reported an over-representation among women 18,[20][21][22][23][24] .…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Menn og kvinner rammes antakelig like ofte (3,4), selv om det i enkelte artikler antydes hyppigere forekomst hos kvinner (5,6). Gjennomsnittlig tid mellom debutsymptomer og rett diagnose er omtrent fire år.…”
Section: Forekomstunclassified